White blood cell count, its subsets, and their indexes in type 2 diabetes mellitus: A mini-review - Klisić, Aleksandra; Kotur-Stevuljević, Jelena; Ninić, Ana (Archives of Pharmacy, 2022)
Due to the increased prevalence of obesity-related complications, especially type 2 diabetes mellitus (DM2), great attention has been paid to the variety of adipokines and cytokines, i.e. biomarkers, which are secreted by the enlarged visceral adipose tissue. Those pro-inflammatory mediators diminish insulin sensitivity via impairing insulin signalling pathways. If these processes persist, insulin resistance and DM2 occur, with a typical finding of low-grade chronic inflammation. The current review focuses on some hematological indices that reflect the inflammation level, such as white blood cell count, its subsets, and derived indexes. Those parameters are easy to measure, cost-effective, and widely available in a primary care setting. A deeper knowledge of the changes in the mentioned hematological parameters in DM2, in addition to glucoregulation biomarkers, may enable physicians to act promptly when patients with this metabolic disorder are concerned.
Keywords: diabetes; leukocytes; obesity; neutrophils; inflammation